Influence of Variable Binary Metal Gate Alloy on the Response Characteristics of Nanoscale Gate All Around MOSFET - Basu*, Suman; Kumar Sarkar, Samir; Kumar Sarkar, Subir (Asian Journal of Chemistry, 2013)
An analytical gate all around (GAA) MOSFET architecture using binary metal gate material is designed in present study. Numerical model is thoroughly studied after solving the 2-D Poisson’s equation with the help of 1-D Poisson’s equation and 2-D Laplace’s equation. 1-D Poisson’s equation and 2-D Laplace’s equation both have been solved with the help of befitting boundary conditions. Parabolic profile of the surface potential is designed in our paper. The mathematical expression of threshold voltage is also established. Moreover effect of variable binary alloy is studied here.